An integrated study of hormone-related sarcopenia for modeling and comparative transcriptome in rats - Shu, Han; Huang, Yubing; Zhang, Wenqian; Ling, Li; Hua, Yuanyuan; Xiong, Zhengai (Frontiers in Endocrinology, 2023)
Sarcopenia is a senile disease with high morbidity, serious complications and limited clinical treatments. Menopause increases the risk of sarcopenia in females, while the exact pathogenesis remains unclear. To systematically investigate the development of hormone-related sarcopenia, we created a model of sarcopenia by ovariectomy and recorded successive characteristic changes. Furthermore, we performed the transcriptome RNA sequencing and bioinformatics analysis on this model to explore the underlying mechanism. In our study, we identified an integrated model combining obesity, osteoporosis and sarcopenia. Functional enrichment analysis showed that most of the significantly enriched pathways were down-regulated and closely correlated with endocrine and metabolism, muscle dysfunction, cognitive impairment and multiple important signaling pathways. We finally chose eight candidate genes to verify their expression levels. These findings confirmed the importance of estrogen in the maintenance of skeletal muscle function and homeostasis, and provided potential targets for further study on hormone-related sarcopenia.